Assessment of Antioxidant Activity of Ethanol Extract from Callyspongia arizusa Obtained from Parentek Beach, Minahasa Regency - Miracle Cristia Meyfi Bambulu; Adithya Yudistira; Erladys Melindah Rumondor (UNIVERSITAS SAM RATULANGI, 2024)
Callyspongia aerizusa is one of the sponges that has compounds with high activity and has a porous body surface structure so that it is included in the phylum porifera. Antioxidants are compounds that work by binding free radicals so that they can inhibit oxidation reactions. This study aims to determine the antioxidant activity of Callyspongia aerizusa. This research is a laboratory experiment by testing the ethanol extract of Callyspongia aerizusa using DPPH (1,1-diphenyl-2-picrylhydrazyl) method. The results of data analysis of % inhibition were 48.9% (100 ppm), 51.09% (120 ppm), 51.32% (140 ppm), 52.00% (160 ppm), and 53.73% (180 ppm). The highest antioxidant activity was achieved at a concentration of 180 ppm with a percent inhibition of 53.73%. This shows that the sample of Callyspongia aerizusa obtained from Parentek Beach, Minahasa Regency has antioxidant activity